Propose of the lens system as a part in development of optical system for Red Ruby Laser Material Cutting Tools / Norazmi Bakar - Bakar, Norazmi (1998)
This project done by doing a case study on propose of the lens system to be implement in the development of optical system for Red Ruby Laser Material Cuttings Tool. The project proposes employing lenses in terms of their types, capabilities and shapes in order to improve the output beam (laser beam). The ultimate aim of the project is to propose the lenses system (obtain by analytical) to be use with Red Ruby Laser Material Cuttings Tool, where Nd-Y AG laser was employed in laboratory experiment as a guidance to examine the practical laser beam.